Dampak Sosial Budaya Pariwisata terhadap Komunitas Lokal di Destinasi Wisata Alam - Ursula Ariyani Darmawan (Tourism and Hospitality Research, 2025)
Tourism development in natural attractions often brings both positive and negative implications for the local communities. This study aims to analyze the sociocultural impacts of tourism on local communities in nature-based tourist destinations in Indonesia. The research uses a qualitative approach with case studies in several national parks and protected forest areas that have become major tourist attractions. Data collection techniques include interviews, observations, and document analysis. The findings reveal that tourism has significantly influenced community behavior, local traditions, and value systems. On one hand, tourism has increased intercultural exchange, income, and education awareness. On the other hand, it has caused commercialization of culture, cultural identity dilution, and social conflicts due to land use and economic inequality. This research contributes to a better understanding of the complexities of tourism development, and suggests that a participatory approach to tourism management involving local communities is crucial to maintain the sociocultural sustainability of destinations. Future studies should consider longitudinal analysis and comparative research across different cultural settings.